6′-O-Caffeoyldihydrosyringin isolated from Aster glehni suppresses lipopolysaccharide-induced iNOS, COX-2, TNF-α, IL-1β and IL-6 expression via NF-κB and AP-1 inactivation in RAW 264.7 macrophages. Issue 19 (1st October 2016) - Seo, Seunghwan; Lee, Kyoung-Goo; Shin, Ji-Sun; Chung, Eun Kyoung; Lee, Jae Yeol; Kim, Hyoung Ja; Lee, Kyung-Tae
Graphical abstract: Abstract: Previously, we found that ethyl acetate extract fraction of Aster glehni exhibited anti-hyperuricemic effects in animal models and also five new caffeoylglucoside derivatives were isolated from this fraction. In this work, we evaluated the anti-inflammatory effects of these caffeoylglucoside derivatives and found that 6′- O -caffeoyldihydrosyringin (2, CDS) most potently inhibited the LPS-induced production of nitric oxide (NO) and prostaglandin E2 (PGE2 ) in RAW 264.7 macrophages. In addition, CDS was found to concentration-dependently reduce the production of NO, PGE2, and the pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), interleukin-1β (IL-1β) induced by LPS in macrophages. Consistent with these observations, CDS concentration-dependently inhibited LPS-induced inducible nitric oxide synthase (iNOS) and cyclooxidase-2 (COX-2) expression at the protein level and also iNOS, COX-2, TNF-α, and IL-6, IL-1β expression at the mRNA level. Furthermore, CDS suppressed the LPS-induced transcriptional activities of nuclear factor-κB (NF-κB) and activator protein-1 (AP-1) as well as the phosphorylation of p65 and c-Fos. Taken together, these results suggest that the anti-inflammatory effect of CDS is associated with the downregulation of iNOS, COX-2, TNF-α, IL-1β, and IL-6 expression via the negative regulation of NF-κB and AP-1 activation in LPS-induced RAW 264.7 macrophages.